Irrigation Water Allocation for Enhanced Productivity and Economic Gain of Haricot Bean (): A Study in Semi-arid Region of Ethiopia - Tatek Wondimu Negash; Abera Tesfaye Tefera; Gebeyehu Ashami Bikila; Aynalem Gurms Dinku; Tigist Worku; Ketema Tezera; Gobena Dirirsa Bayisa (Air, Soil and Water Research)
This study aimed to evaluate the impact of varying irrigation levels on haricot bean yield and its related attributes. The experiment was conducted with five irrigation treatments: 60%, 80%, 100%, 120%, and 140% Manageable Allowed Depletion (MAD). The results revealed that the 80% MAD treatment produced the highest haricot bean yields, with 25.03, 26.07, and 23.46 qt/ha in 2016, 2017, and 2018, respectively, with no significant difference from the 100% MAD treatment. The lowest yields per hectare were observed under the 140% MAD treatment, with yields of 18.05, 18.6, and 15.45 qt/ha respectively, across the same years. The average maximum yield across all 3 years was 24.84 qt/ha for the 80% MAD treatment, whereas the minimum was 17.36 qt/ha for the 140% MAD treatment. Water productivity was lowest at 4.32 kg/mm for the 60% and 140% MAD treatments, while the highest values were recorded at 6.09 and 6.07 kg/mm for the 100% and 80% MAD treatments, respectively. Economically, the 80% MAD treatment yielded the highest economic gain of 30,193.1 birr/ha. Therefore, based on these findings, applying 80% MAD under furrow irrigation is recommended for optimal haricot bean production in the semi-arid regions of Ethiopia and similar environments.